Tekening uit een onbekend boek van Nienke van Hichtum (het pseud. van S. Troelstra Bokma de Boer) - Jetses, C., (1903)
Tekening uit een onbekend boek van Nienke van Hichtum (het pseud. van S. Troelstra Bokma de Boer).